Zulu - Caine, Michael; Hawkins, Jack; Jacobsson, Ulla; Booth, James; Stanley, Baker (UK : Paramount Home Entertainment, 1964)
Zulu is one of the greatest historical action movies ever made, and one of the great war movies. It is based on what historian Michael Glover terms "the most highly decorated battle in British history", the defence of Rorke's Drift during the Zulu War of 1879. Eleven of the defenders received Britain's highest award for military valor, the Victoria Cross--the rarely awarded counterpart of the US Medal of Honor. The movie is a landmark in the art of cinema for its extraordinary combination of location, cross-cultural engagement, a real story, good script, fine cast and great production team. This 1964 film never looks tired, despite my many years of rerunning it in 16mm, the Criterion laserdisc, later the Front Row Entertainment Inc. DVD, and then the Paramount DVD and Blu-ray discs. Anecdotally, military colleges have used Zulu to show the power of directed massed musketry, and leadership and teamwork in combat.
Based on an actual historic event, this is the story of a group of British soldiers stationed in Africa who are forced to defend their tiny outpost against an attack by powerful Zulu warriors. They are outnumbered 40-1 but are still ready to fight to the finish.
Eng & German
Keywords: Movie -- British solidiers; Zulu land